Caracterización y evaluación de la resistencia a la corrosión de películas delgadas de oxinitruro y/o óxido de cerio sobre AISI 316l (2020)
Through the sputtering technique, cerium oxynitride and / or cerium oxide films were synthesized on AISI 316L surgical steel. In total 8 deposit conditions were planned under which the temperature (180, 200, 250 and 300 ° C) and the nitrogen flow (15.0 and 20.0 sccm) were changed. Additionally, the results of morphology and corrosion resistance were compared with those of zirconia oxynitride films and nickel copper oxynitrides which are known to improve the corrosion resistance of surgical grade stainless steel and favor osteoblast cell growth. The latter were deposited under previously standardized conditions within the research group. CeO2 and / or CeOxNy, ZrOxNy and NiCuON films were morphologically, chemically and structurally characterized by SEM, EDX and DRX. Zirconium and nickel copper oxynitride have a homogeneous morphology with good adhesion, without micropores and microcracks; while those of CeO2 and / or CeOxNy, are characterized by having a large number of surface defects and low adhesion to the substrate in some of the selected deposit conditions. Those deposited at a temperature of 200 ° C and nitrogen flow N2 = 20.0 sccm, presented the best morphology, with little delamination, micropores and microcracks. As for the crystalline structure of the CeO2 and / or CeOxNy films, it was cubic with preferential growth on the planes (111) and (220) of CeO2. The corrosion resistance results evaluated from EIS electrochemical impedance spectroscopy and potentiodynamic polarization curves show that despite the surface defects of the CeO2 and / or CeOxNy films, all the test pieces presented impedance values, Corrosion current density, polarization resistance, corrosion potential and pitting nucleation, better than bare 316L stainless steel, suggesting that the cerium ceramic coating would induce galvanic protection of the steel. The films deposited at 200 ° C and flow of N2 = 20.0 sccm presented the greatest protection against corrosion in Hank's solution. The results obtained in this work are a contribution to the development of surgical steel surface coatings for biomedical applications.